Corporate Income Tax Avoidance in the European Arena – Evidence and Remedies - Pál, Tibor; Tóth, Zsófia (Theory, Methodology, Practice – Review of Business and Management, 2015)
According to the OECD, 4% to 10% of the global corporate income tax revenue, i.e. USD 100 to 240 billion annually, is lost due to corporate income tax avoidance (OECD, 2015). Although the existence of the issue is well-accepted by the tax policy makers of the developed world, it is extremely difficult to agree on an international tax policy standard which could reduce the vulnerability of the sovereign tax regimes. In this article, we summarize the historical background of corporate income tax avoidance, and provide evidence of its existence in the EU member states. In addition, we also examine a new international income tax model proposed by the European Commission and analyse the expected effects of the proposal onthe risk associated with tax avoidance in Europe.